An improved regioselective preparation of methyl 2,3-di-O-acetyl-α, β-d-xylofuranoside - Gudiño, Esteban Dario; Iribarren, Adolfo Marcelo; Iglesias, Luis Emilio (Biocatalysis and Biotransformation)
Methyl 2,3-di-O-acetyl-α,β-d-xylofuranoside was prepared as the sole regioisomer in 6372% yield, according to the applied mass of substrate, through a Candida antarctica lipase B catalysed alcoholysis of methyl 2,3,5-tri-O-acetyl-α,β-d-xylofuranoside. The product is a potential synthetic precursor for 5-modified xylofuranosides and 5′-modified xylonucleosides. Fil: Gudiño, Esteban Dario. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología. Área Química. Laboratorio de Biotransformaciones; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Iribarren, Adolfo Marcelo. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología. Área Química. Laboratorio de Biotransformaciones; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones en Ingeniería Genética y Biología Molecular "Dr. Héctor N. Torres"; Argentina Fil: Iglesias, Luis Emilio. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología. Área Química. Laboratorio de Biotransformaciones; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina